Расчет спектра нейтронов облученного топливного блока ВГТРУ; Будущее атомной энергетики - Луцик И. О. Игорь Олегович; Беденко С. В. Сергей Владимирович; Губайдулин И. M. Ильдар Мухарамович; Шаманин И. В. Игорь Владимирович (2017, 2017)
Заглавие с экрана